Remarks During Press Call on 100 Countries Milestone for COVID-19 (Coronavirus) Emergency Health Support - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank, discussed the severe health and economic impacts that the Coronavirus 2019 (COVID-19) pandemic and shut down have inflicted on developing countries. The World Bank Group’s goal was to provide rapid, flexible responses to developing countries. That’s a way to protect the poorest, by providing cash and other expandable support on debt, also to maintain the private sector and bolster the economic recovery. He announced that the World Bank Group will finance emergency programs in 100 countries - that’s home to 70 percent of the world’s population. The programs are tailored to the countries to effectively respond to the health, economic, and social shocks that that country are facing. On May 1 the Bank marked the start of an official bilateral debt payment suspension for International Development Association (IDA) countries, those that request forbearance. It is an initiative launched with the International Monetary Fund (IMF’s) Managing Director in March and it was quickly endorsed by the G20 countries.